Analysis of the viscosity reduction of crude oil with nano-Ni catalyst by acoustic cavitation. (1st September 2020) - Cui, Jingjing; Zhang, Zhihong; Liu, Xuedong; Liu, Lin; Peng, Jian
Abstract: The present study discusses ultrasound wave and heterogeneous catalysts act synergistically on viscosity reduction of crude oil. The reasons for the possible viscosity reduction were analyzed from the structural changes of asphaltene. This paper presents a systematic and unified approach to analyzing asphaltene clusters structure based on FTIR spectra and XRD patterns. The results reveal that the cavitation effect can be intensified by the addition of metallic nickel particles. The cavitation effect destroys the spatial network structure formed by resin, asphaltene and wax crystals, so that the viscosity of the treated oil sample tends to be stable. With the addition of metallic nickel particles which has a synergistic effect on cavitation, the asphaltene molecules have undergone a cracking reaction and decomposed into small molecular hydrocarbon compounds, contributing to viscosity reduction. However, when added a certain amount of metallic nickel particles, the degree of surface cavitation leads to increasing number of cavitation bubbles, free radicals recombination, and aromatic hydrocarbons polymerizing to form secondary asphaltenes. This leads to a slight rise in viscosity.